Substitution rate comparisons between grasses and palms: synonymous rate differences at the nuclear gene Adh parallel rate differences at the plastid gene rbcL. - Gaut, B S (1996)
A number of studies have noted that nucleotide substitution rates at the chloroplast-encoded rbcL locus violate the molecular clock principle. Substitution rate variation at this plastid gene is particularly pronounced between palms and grasses; for example, a previous study estimated that substitution rates in rbcL sequences are approximately 5-fold faster in grasses than in palms. To determine whether a proportionate change in substitution rates also occurs in plant nuclear genes, we characterized nucleotide substitution rates in palm and grass sequences for the nuclear gene Adh. In this article, we report that palm sequences evolve at a rate of 2.61 x 10(-9) substitution per synonymous site per year, a rate which is slower than most plant nuclear genes. Grass Adh sequences evolve approximately 2.5-fold faster than palms at synonymous sites. Thus, synonymous rates in nuclear Adh genes show a marked decrease in palms relative to grasses, paralleling the pattern found at the plastid rbcL locus. This shared pattern indicates that synonymous rates are correlated between a nuclear and a plastid gene. Remarkably, nonsynonymous rates do not show this correlation. Nonsynonymous rates vary between two duplicated grass Adh loci, and nonsynonymous rates at the palm Adh locus are not markedly reduced relative to grasses.